2022
DOI: 10.7554/elife.76923
|View full text |Cite
|
Sign up to set email alerts
|

A native chemical chaperone in the human eye lens

Abstract: Cataract is one of the most prevalent protein aggregation disorders and still the most common cause of vision loss worldwide. The metabolically quiescent core region of the human lens lacks cellular or protein turnover; it has therefore evolved remarkable mechanisms to resist light-scattering protein aggregation for a lifetime. We now report that one such mechanism involves an unusually abundant lens metabolite, myo-inositol, suppressing aggregation of lens crystallins. We quantified aggregation suppression us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…There is no treatment for cataracts beyond eye surgery, which is not risk-free and represents a high cost that amounts to billions of dollars per year. In developing countries, lack of access to cataract surgery makes this disease a major cause of visual disability …”
Section: Introductionmentioning
confidence: 99%
“…There is no treatment for cataracts beyond eye surgery, which is not risk-free and represents a high cost that amounts to billions of dollars per year. In developing countries, lack of access to cataract surgery makes this disease a major cause of visual disability …”
Section: Introductionmentioning
confidence: 99%
“…Earlier in our lab, we found that the lenses of another nocturnal animal, the Rat ( R. norvegicus ), contain high concentrations of taurine, which prevails almost tenfold over myo -inositol (13.2 and 1.8 µmol/g correspondingly) [ 33 ]. It has been also recently suggested [ 48 ] that, besides osmotic protection, myo -inositol in the eye lens may act as a chaperone, protecting the lens proteins from the aggregation caused by post-translational modifications during a lifespan. Most likely, low levels of myo -inositol in owl lenses should be attributed to their nocturnal lifestyle, so the light-induced protein modifications for these species are less dangerous.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies by others have reported the existence of small molecules that bind to γcrystallins including lanosterol (61), cochineal carmine (62), orthovanilin (63), quercetin (64), hesperetin (65) and sodium citrate (66). Moreover, small molecules with either demonstrated or potential anticataract properties involving anti-aggregation activity against crystallins include rosemarinic acid (67), morin (68,69), 25-hydrocholesterol(70),EGCG (71) and myoinositol (72). Among these compounds, those that were included in the screen included EGCG, which improved aggregation, while morin, lanosterol, hesperetin and carmine had no impact.…”
Section: Discussionmentioning
confidence: 99%